Possibilities of using the 3D printing process in the concrete and geopolymers application. (November 2019) - Marczyk, J; Ziejewska, C; Łach, M; Korniejenko, K; Lin, W T; Hebda, M
Abstract: Additive manufacturing, also known as three-dimension printing (3DP) has a lot of advantages over traditional construction technology, including high building efficient, less construction wastes and greatly reduced labor. This paper presents the possibility of applying this technique to 3D printing of geopolymers and concrete. Moreover, a general overview of the research and progress of 3D printing of geopolymers and concrete in recent times was characterized. This paper also identifies the most interesting and innovative solutions in this area and highlights emerging trends to stimulate further research.